Music Stimuli Recognition in Electroencephalogram Signal - Suto, Jozsef; Oniga, Stefan (Elektronika ir Elektrotechnika, 2018)
When humans are listening to music they perceive beats, rhythms and melodies. Music stimuli induce motor system activities and it has a powerful emotion trigger effect. Since music is a potential stimulus in electroencephalogram based emotion research we supposed that different kinds of songs are recognizable from electroencephalogram signal. In this study we try to recognize music-induced electroencephalogram responses with the popular Neurosky Mindwave device. This paper describes the test conditions and the efficiency of an artificial neural network in combination with different data pre-processing techniques. The final outcomes show the negative effect of frequency decomposition and that the meditation level has more significant effect on the recognition than a particular song.DOI: http://dx.doi.org/10.5755/j01.eie.24.4.21482